Musculoskeletal Pain and Compensatory Mechanisms in Posture and Adaptation to Sport in Players from the Polish Men’s Goalball National Team—Cross Sectional Study - Barbara Rosołek; Dan Iulian Alexe; Diana Celebańska; Anna Zwierzchowska (Applied Sciences)
The aim of the study was to verify the relationship between musculoskeletal pain of elite Polish goalball players and selected physique and posture characteristics. We examined 12 players. The mean age was 21.8 ± 6.0 years, and a mean training experience of 6.3 ± 3.4 years. Physique (body mass, body height, waist circumference, fat tissue, fat-free soft tissue) and posture (thoracic kyphosis and lumbar lordosis) and range of motion (in the thoracic and lumbar regions) were assessed. The incidences and locations of musculoskeletal pain were identified using the Nordic Musculoskeletal Questionnaire, covering the period from the last seven days (NMQ-7) and six months (NMQ-6). Due to the small group size, non-parametric tests (Spearman’s rank correlation) were used. The significance level was set at p < 0.05. Players were more likely to report musculoskeletal pain in the last six months than in the previous week. Pain reported in both NMQ6 and NMQ7 was most common in the wrists/hands and lower back, and, in NMQ6, also in the shoulders and ankles/feet. There were significant negative correlations of total NMQ7 with lumbar lordosis angle in the habitual standing position (R = −0.6; p = 0.04), trunk flexion (R = −0.8, p = 0.002), and trunk extension (R = −0.6; p = 0.03), and a positive correlation with thoracic kyphosis angle in trunk flexion (R = 0.8, p = 0.005). There was a statistically significant, inversely proportional relationship of thoracic kyphosis angle values in the habitual position (R = −0.58; p = 0.049) and thoracic kyphosis angle THA in trunk flexion (R = −0.6; p = 0.038) with time of disability. Relationships between some body posture parameters and musculoskeletal pain in the studied athletes were also noted.